Multitissue single-nucleus RNA-seq reveals cell type–specific regulatory patterns of alternative polyadenylation in pigs - Wen, Qiuhan; Wang, Zhen; Bao, Qi; Ding, Tianli; Zhang, Haihan; Li, Jianbo; Liu, Zhuang; Huang, Jieping; Yi, Guoqiang (Genome Research, 2025)
As an important posttranscriptional modification mechanism, alternative polyadenylation (APA) plays a crucial role in gene regulation and phenotypic diversity. Whereas extensive studies have explored the global APA landscape using bulk RNA-seq data, in-depth analyses of APA events at the single-cell level remain limited—particularly in farm animals. In this study, we construct a comprehensive APA atlas for 261 cell types across 19 porcine tissues based on single-nucleus RNA sequencing (snRNA-seq) data. This analysis reveals tissue- and cell type–specific patterns of APA. We find that many genes display a clear correlation between the average length of 3′ untranslated regions (3′ UTRs) and expression levels in various cell types, with most showing a negative correlation. Early cell types within the developmental lineage, such as spermatogonia and satellite cells, display longer 3′ UTRs, especially for spermatogenesis, where 3′ UTR lengths show significant decreasing trends along the differentiation trajectory. Notably, we find that variable 3′ UTR lengths in the CD47 and GPD1 genes might be critical regulators during spermatogenesis and myogenesis, respectively, potentially through modulation of RNA-binding protein and miRNA binding sites. Furthermore, the SNP rs323354626, located in the 3′ UTR of the CD47 gene, significantly impacts gene splicing and is strongly associated with reproductive phenotypes. Additionally, we observe that neuronal cells generally possess longer 3′ UTRs—a pattern conserved across humans, mice, fruit flies, and pigs. Together, these findings enrich the single-cell atlas of pigs by adding a layer of posttranscriptional regulation to the existing gene expression data, highlighting the significant role of cell type–specific 3′ UTR lengths in cell commitment and complex trait regulation.
10.1101/gr.280095.124